Regression Testing Systematic Literature Review â€“ A Preliminary Analysis - Ba-Quttayyan, Bakr; Mohd, Haslina; Baharom, Fauziah (International Journal of Engineering and Technology, 2018)
Software needs to be modified and frequently maintained by what is called regression testing. Regression testing is a costly but necessary maintenance activity in the software development lifecycle (SDLC), which can be performed to revalidate modified software to make sure that changes did not adversely affect software behavior. Several studies have been carried out regarding regression testing domain in the literature. However, these studies need to be classified, summarized and ordered in a systematic manner to spot on the current state of the art of regression testing field. Previously, a protocol for conducting systematic literature review for regression testing was carried out. Therefore, this paper will carry out a systematic literature review (SLR) to illustrate the current state-of-the-art of regression testing domain. In this SLR, a manual search has been conducted to obtain related studies from four various sources where those studies were classified under journal, conference proceeding, and book chapter categories within specific criteria. Consequently, the initial search resulted in 1261 unfiltered studies, which then decreased according to certain predefined criteria up to 246 selected relevant studies. For the next stage, primary and secondary studies were identified. As a result of this stage, major regression testing concepts such as: approaches, frameworks, models and tools were briefly presented, analyzed and discussed in related with selected studies. In the future, regression testing approaches, techniques and tools will be further discussed in more detail.Â Â
Keywords: Regression testing; software maintenance; systematic review; software testing.